2020
DOI: 10.1136/svn-2020-000391
|View full text |Cite
|
Sign up to set email alerts
|

Staged angioplasty versus regular carotid artery stenting in patients with carotid artery stenosis at high risk of hyperperfusion: a randomised clinical trial

Abstract: Background and purposeHyperperfusion (HP) is a devastating complication associated with carotid artery stenting (CAS) or endarterectomy. The efficacy and safety of staged angioplasty (SAP) in patients with CAS at high risk of HP remains unclear. We sought to determine whether SAP is superior to regular CAS in patients with high risk of HP.MethodsA randomised, multicentre open-label clinical trial with blinded outcome assessment (STEP) was conducted. Patients with severe carotid stenosis at high risk of HP were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Ten studies were included in this meta-analysis. Among these, one article was randomized control trial 8 and nine articles were non-RCTs (four non-controlled studies 1417 and five case-control studies 4 , 6 , 911 ). The main characteristics of the included studies are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies were included in this meta-analysis. Among these, one article was randomized control trial 8 and nine articles were non-RCTs (four non-controlled studies 1417 and five case-control studies 4 , 6 , 911 ). The main characteristics of the included studies are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are provided in Table 1. Four studies included all patients with symptomatic carotid stenosis (defined as carotid stenosis associated with stroke or transient ischaemic attack), 8 , 14 , 16 , 17 four studies included patients with asymptomatic or symptomatic carotid stenosis, 6 , 9 , 11 , 15 and two studies only included patients with carotid stenosis without reference to asymptomatic or symptomatic stenosis. 4 , 10 Eight studies reported on elective procedures only, 4 , 6 , 911 , 1517 two studies might recruit acute patients based on the description of their method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations